Internalisasi Nilai-Nilai Keagamaan Perilaku Peserta Didik: Studi Kegiatan Positif di Lingkungan MTs Unggulan Al-Jadid Waru Sidoarjo - Amir Bandar Abdul Majid; Zhunnun Qothrunnada Annisa Salam Al Madury; Istifaiyyatul Qudsi (Journal of Innovative and Creativity, 2025)
This study aims to examine the efforts of the academic community at MTs Unggulan Al-Jadid Waru Sidoarjo in internalizing religious values among students through various positive activities within the school environment. The research focuses on the methods or strategies used to internalize these values through positive activities. A qualitative approach with field study methods was employed in this research. Data were collected through interviews and observations. The findings reveal that the internalization process is carried out through habituation and a deep understanding of belief values and Islamic norms, reflected in routine activities such as 5S (Smile, Greeting, Salutation, Politeness, and Courtesy), recitation of prayers and the Qur'an before lessons, congregational prayers, commemoration of Islamic holidays, and religious extracurricular activities. The academic community employs a holistic strategy that includes integrating a values-based curriculum, habituation through daily routines and extracurricular activities, as well as role modeling from all members of the academic community. Effective communication between the school, students, and parents is also a crucial factor in supporting the internalization of religious values. Although there is no specific written plan, the school has successfully integrated religious values into various daily activities and provided role models from the entire academic community, thus shaping students' character to be religious, disciplined, and morally upright.